A Mental Health Guide For Older Kansans And Their Families - Carman, Mary; Trout, Nancy; Norris-Baker, Lyn; Johannes, Elaine; Scarpelli, Anicia (My University, 2000)
This publication provides resoucres about mental health problems and mental health services for use by older Kansans, their families, and non-mental health service providers.
MF2447_2000_01
Keywords: MF2447; Home and Family; Health and Safety; MF